In the Global Epicenter: Social Work Leadership in a New York City Hospital. (2nd January 2021) - Xenakis, Nancy; Brosnan, Mary M.; Burgos, Laudy; Childs, Jocelyn; Deschamps, Julia; Dobrof, Judith; Farquhar, Diane Weg; Genovesi, Maya L.; Goldgraben, Kaitlin R.; Gordon, Elisa; Hamilton, Christine; Koppel, Sarah R.; et al.
ABSTRACT: The Mount Sinai Hospital in New York City was in the epicenter of the COVID-19 pandemic and had to transform from a tertiary to crisis care hospital and increase its bed capacity by 50 percent to care for COVID-19 patients. The size, scope, complexity and uncertainty of this crisis was unparalleled. This article describes the comprehensive response of the Department of Social Work Services, one of the largest hospital social work departments in the country. The response was informed by four Departmental principles, as well as crisis intervention strategies. This article describes organizational structures, practice models, policies, and protocols developed to respond quickly and effectively, given infection prevention mandates, to patient, population and workforce needs. Finally, it includes how social workers addressed COVID-19 related physical and psychosocial needs and applied and modified interprofessional communication and collaboration. Lessons learned and clinical and administrative changes that will assist in navigating "new normal" operations are discussed.